Dire Necessity and Transformation: Entry‐points for Modern Science in Islamic Bioethical Assessment of Porcine Products in Vaccines. (28th February 2013) - Padela, Aasim I.; Furber, Steven W.; Kholwadia, Mohammad A.; Moosa, Ebrahim; Ghaly, Mohammed
Abstract The field of medicine provides an important window through which to examine the encounters between religion and science, and between modernity and tradition. While both religion and science consider health to be a 'good' that is to be preserved, and promoted, religious and science‐based teachings may differ in their conception of what constitutes good health, and how that health is to be achieved. This paper analyzes the way the Islamic ethico‐legal tradition assesses the permissibility of using vaccines that contain porcine‐derived components by referencing opinions of several Islamic authorities. In the Islamic ethico‐legal tradition controversy surrounds the use of proteins from an animal (pig) that is considered to be impure by Islamic law. As we discuss the Islamic ethico‐legal constructs used to argue for or against the use of porcine‐based vaccines we will call attention to areas where modern medical data may make the arguments more precise. By highlighting areas where science can buttress and clarify the ethico‐legal arguments we hope to spur an enhanced applied Islamic bioethics discourse where religious scholars and medical experts use modern science in a way that remains faithful to the epistemology of Islamic ethics to clarify what Islam requires of Muslim patients and healthcare workers.